2019
DOI: 10.2754/avb201988040425
|View full text |Cite
|
Sign up to set email alerts
|

The electrophoretic pattern of serum proteins in dogs with babesiosis

Abstract: This study was aimed at the evaluation of the electrophoretic pattern of serum proteins in dogs naturally infected with Babesia canis. Blood samples were collected from 37 dogs infected with B. canis and showing clinical signs consistent with the disease. The sick animals were classified as dogs with physiologic and decreased red blood cell (RBC) values. Twenty-five healthy dogs formed the control group. The concentrations of total proteins and protein fractions were measured in blood serum. The values of tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…In the relative concentrations of β-globulins, no significant differences were observed between the dogs infected with B. gibsoni and all dogs with B. canis infection, except for β 1 -globulin fraction in complicated form of B. canis infection. The values were higher than those obtained by Tóthová et al 16 in clinically healthy dogs. The infection with Babesia parasites activates the mechanisms of the non-specific immune responses of the host, including the complement pathway with increased synthesis of complement components, especially C3a 45 , 46 .…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In the relative concentrations of β-globulins, no significant differences were observed between the dogs infected with B. gibsoni and all dogs with B. canis infection, except for β 1 -globulin fraction in complicated form of B. canis infection. The values were higher than those obtained by Tóthová et al 16 in clinically healthy dogs. The infection with Babesia parasites activates the mechanisms of the non-specific immune responses of the host, including the complement pathway with increased synthesis of complement components, especially C3a 45 , 46 .…”
Section: Discussioncontrasting
confidence: 75%
“…The alterations in the serum protein electrophoretic pattern in dogs following natural infection with B. canis were studied previously by Maegraith et al 37 and Tella and Maegraith 38 , and recently by Lobetti et al 39 and Tóthová et al 16 , while a decrease in the relative concentrations of albumin was a typical finding in these studies. Furthermore, Tóthová et al 16 recorded significantly higher relative concentrations of α 1 -, β 1 - and β 2 -globulins, and non-significantly higher values of α 2 - and γ-globulins in the affected dogs with a double α 2 -zone in six from thirty-seven evaluated animals. On the other hand, the findings of the study conducted by Lobetti et al 39 showed in dogs with mild and severe babesiosis low total serum proteins, albumin, A/G ratio and α-globulins, whereas dogs with complicated babesiosis had no typical alterations in the serum protein pattern.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Also, a pronounced change in the serum biochemical parameters of infected dogs was an increase in the content of globulins α-1, α-2 and βfractions, which are essential proteins of the so-called "acute phase" (Tothova et al, 2019). Such changes characterize the body's fight against foreign agents in response to infection.…”
Section: Discussionmentioning
confidence: 99%